Econometric Analysis of the Determinants of Rice Farming Systems Choice in Côte d'Ivoire. (May 2022) - Ouattara, N'Banan; Xiong, Xueping; Guo, Chenguang; Traoré, Lacina; Ballo, Zié
In sub-Saharan African countries, rice is grown through different rice farming systems (RFSs). Despite the growing interest of policymakers and significant research in ensuring sustainable rice production, little is known about the factors that underline the choice of the different RFSs. This study empirically examines key determinants of RFSs choice with Côte d'Ivoire, a case study, where three rice production systems are distinguished. Considering that farmers can make multiple choices, we use a Multivariate Probit model. Data were collected from 588 rice farmers randomly sampled in seven rice areas. The results show that the determinants of the choice of RFSs vary from one production system to another. More specifically, land tenure, presence of an irrigation system, intercropping system, access to extension services, membership in a rice farmers' organization, access to credit, paddy rice marketing, rice farm size, farming experience, off-farm income, gender, and household size influence the choice of the different RFSs. Our results suggest increasing investment in irrigation infrastructure, strengthening technical and organizational support to rice farmers, and defining guidelines for the intercropping system.